The EPINetz Twitter Politicians Dataset 2021. A~New Resource for the Study of the German Twittersphere and Its Application for the 2021 Federal Elections - Tim König; Wolf J. Schünemann; Alexander Brand; Julian Freyberg; Michael Gertz (Politische Vierteljahresschrift, 2022)
This research note introduces the EPINetz Twitter Politicians Dataset, a~comprehensive dataset of 2449 Twitter accounts of German parliamentarians, minsters, state secretaries, parties, and ministries on a~state, federal, and European Union level for the year 2021. This hand-curated dataset not only provides up-to-date information on elected officials, but it also includes additional variables such as their party affiliation, age, and gender. Furthermore, it provides linkages to additional data sources by providing the accounts' Wikidata and Abgeordnetenwatch (Parliamentwatch) IDs. While it does not provide actual tweet data, the dataset will be a~valuable resource for researchers by providing easy access to elected German politicians. We demonstrate some of the dataset's uses with an analysis of the 2021 German Federal Elections. The full dataset can be accessed via https://doi.org/10.7802/2415 .
Keywords: 320; Social Media; Germany; Data; Political communication; Political representatives; Election campaigns; Soziale Medien; Deutschland; Daten; Politische Kommunikation; Politische Repräsentanten; Wahlkampf